(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article investigates comparative and equivalence relations between synonymic series in English and Uzbek. Drawing on componential, contextual, and contrastive methods of analysis, the study examines how synonymic units in the two languages align semantically, stylistically, and pragmatically. The findings reveal that full interlingual equivalence between synonymic series is relatively rare; partial and contextual equivalence constitute the dominant patterns, shaped by register constraints, collocational preferences, and cultural-cognitive factors. The study identifies zones of interlingual asymmetry and lexical lacunae that pose significant challenges for translation and bilingual pedagogy. Theoretical and practical implications are discussed for comparative lexicology, translation studies, and English as a Foreign Language (EFL) instruction.